2016
DOI: 10.1111/jfpp.12821
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoplasmic Protein Hydrolysis Activity ofLactobacillus plantarum120 Isolated from Suanyu: A Traditional Chinese Low Salt Fermented Fish

Abstract: The hydrolysis of sarcoplasmic proteins during the growth of Lactobacillus plantarum 120 originally isolated from Suanyu, a traditional Chinese low salt fermented fish, was evaluated. Fermentation was carried out in a fish meat model system at 30C for 96 h. Proteolytic activity of this strain on fish muscle sarcoplasmic protein was determined by proteins, peptides and free amino acids analyses. There was a pronounced hydrolysis of almost all protein bands in electrophoretic pattern by L. plantarum 120. It also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 39 publications
2
20
1
Order By: Relevance
“…Further hydrolysis of sarcoplasmic proteins and generation of peptides and free amino acids is attributed to enzymes of microbial origin, as well as to the remaining activity of the endogenous meat enzymes (Candogan et al, 2009). Similar conclusions have also been made by Wang et al (2017) during the assessment of the degree of fish sarcoplasmic proteins by Lactobacillus plantarum 120. Starting from the second experimental period (90 days), the content of primary amino groups increased, and the increase was greater in samples with probiotic strains of LAB than in the sample undergoing spontaneous fermentation (P < 0.01).…”
Section: Proteolysis Degree Of Muscle Protein Fractionssupporting
confidence: 61%
See 1 more Smart Citation
“…Further hydrolysis of sarcoplasmic proteins and generation of peptides and free amino acids is attributed to enzymes of microbial origin, as well as to the remaining activity of the endogenous meat enzymes (Candogan et al, 2009). Similar conclusions have also been made by Wang et al (2017) during the assessment of the degree of fish sarcoplasmic proteins by Lactobacillus plantarum 120. Starting from the second experimental period (90 days), the content of primary amino groups increased, and the increase was greater in samples with probiotic strains of LAB than in the sample undergoing spontaneous fermentation (P < 0.01).…”
Section: Proteolysis Degree Of Muscle Protein Fractionssupporting
confidence: 61%
“…Similar conclusions have also been made by Wang et al . () during the assessment of the degree of fish sarcoplasmic proteins by Lactobacillus plantarum 120. Starting from the second experimental period (90 days), the content of primary amino groups increased, and the increase was greater in samples with probiotic strains of LAB than in the sample undergoing spontaneous fermentation ( P < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the evidence, the IB1C and IB3B isolates were considered as L. plantarum species, and IB3E and IB3F isolates were considered as P. pentosaceus. The similar studies about the isolation of lactic acid bacteria from fish fermentation products were reported that antimicrobial compound produced by L. plantarum and P. pentosaceus (Desniar et al 2015;Budiarto et al 2016;Wang et al 2016).…”
Section: Identification Of the Antimicrobial-producing Strainmentioning
confidence: 83%
“…Several studies on the isolation of the LA from fish fermentation products also showed similar results. Wang et al (2016) in their study succeeded in isolating L. plantarum 120 from fish fermentation product from China, Suanyu. L. plantarum JCM-1149 produce antimicrobial compounds that inhibit the growth of Listeria monocytogenes (Nursyam et al 2016).…”
Section: Identification Of the Antimicrobial-producing Strainmentioning
confidence: 99%
“…The implementation of this type of biological technology provides alternative ways for several of these by-products to be treated [19,20]. For example, LAB can be used to break down collagen structures from the carcasses of the meat industry, and specialized compounds from lignocellulosic biomass fermentation can produce metabolites that can be implemented in the elaboration of detergents [21][22][23].…”
Section: Introductionmentioning
confidence: 99%